Blockchain Technology in Pharmaceutical Industry: A Review of Recent Research Articles on PubMed: An Evolving Paradigm - Pareek, Varun; Saran, Divya; Sharma, Lokendra; Jakhar, Punam; Kumar, Susheel (Scripta Medica, 2024)
Blockchain technology has emerged as a formidable force ready to transform the pharmaceutical business. This study investigated the integration of smart contracts and decentralised apps as potential future possibilities, emphasising their ability to automate crucial operations and strengthen pharmaceutical product integrity, based on the recently published articles in PubMed between 2015 to 2023 with “pharmacology” and “blockchain” as search keywords. Recent study backed up the idea that blockchain can improve openness, security and efficiency in the industry. According to research, it has the ability to speed up regulatory approvals while also considerably reducing the risk of counterfeit medications penetrating the supply chain. Furthermore, the ability of blockchain to disrupt existing intermediaries and enable disintermediation may result in a more streamlined and efficient industry. While there are implementation obstacles, the benefits of this technology in medicines are significant. Embracing blockchain promises a future of increased security, transparency and patient-centricity, ultimately changing healthcare. This article explored blockchain application in the pharmaceutical sector with innovations like Medledger and chaincodes, addressing drug tracing and supply chain security. It presents a structure for a private network using Hyperledger Fabric, showcasing blockchain’s potential to enhance transparency, security and efficiency beyond traditional areas.